THE A (H1N1) INFLUENZA. SYMBOLIC DIMENSIONS OF A PANDEMIC ARTEFACT (Sociología y tecnociencia, 2013)
The aim of the present paper is to present the symbolic features that are exposed by the concept of artefact in the context of a pandemic alarm, such as the A (H1N1) influenza. The symbolic qualities entailed by the notion of artefact are well-known within the Social Sciences: Sociology, Anthropology, Archaeology, and Linguistics. The artefact is basically not an object, but an action aimed at designing, simulating or creating a simile by means of material, technological or linguistic structures. The purpose of the present work is to unveil the symbolic dimensions that are activated by the A (H1N1) influenza as a Pandemic Artefact: a) the assumption of separating information from matter; b) the need for a material support to enable the exchange; c) the sociological reflexivity of the artefact and its agency; d) the arbitrariness of its social use, that detaches it from the design as intention.